Relationship between pre-extubation positive endexpiratory pressure and oxygenation after coronary artery bypass grafting - Lima,Reijane Oliveira (2015)
Abstract Introduction After removal of endotracheal tube and artificial ventilation, ventilatory support should be continued, offering oxygen supply to ensure an arterial oxygen saturation close to physiological. Objective: The aim of this study was to investigate the effects of positive-end expiratory pressure before extubation on the oxygenation indices of patients undergoing coronary artery bypass grafting. Methods: A randomized clinical trial with seventy-eight patients undergoing coronary artery bypass grafting divided into three groups and ventilated with different positive-end expiratory pressure levels prior to extubation: Group A, 5 cmH2O (n=32); Group B, 8 cmH2O (n=26); and Group C, 10 cmH2O (n=20). Oxygenation index data were obtained from arterial blood gas samples collected at 1, 3, and 6 h after extubation. Patients with chronic pulmonary disease and those who underwent off-pump, emergency, or combined surgeries were excluded. For statistical analysis, we used Shapiro-Wilk, G, Kruskal-Wallis, and analysis of variance tests and set the level of significance at P<0.05. Results Groups were homogenous with regard to demographic, clinical, and surgical variables. There were no statistically significant differences between groups in the first 6 h after extubation with regard to oxygenation indices and oxygen therapy utilization. Conclusion: In this sample of patients undergoing coronary artery bypass grafting, the use of different positive-end expiratory pressure levels before extubation did not affect gas exchange or oxygen therapy utilization in the first 6 h after endotracheal tube removal.